Peran Serikat Petani Indonesia Dalam Mewujudkan Kedaulatan Pangan Di Provinsi Banten - Ikhsan Tri Santoso; Wahyu Kartiko Utami (Epistemik Press, 2022)
This research contains the role of the Serikat Petani Indonesia in realizing food sovereignty in Banten Province. This study also explains agricultural issues such as the decline in the number of farmers in Banten, the rate of land conversion, and the farmers exchange rate. The purpose of this study is to understand and support the efforts of the serikat petani Indonesia in actualized food sovereignty in Banten Province and as an information and campaigns to the public regarding the importance of actualized food sovereignty. This research uses development farm theory by Pareke and advocacy by Sheila Espone. This research uses a qualitative method with a descriptive approach. The results of this research explain the efforts of serikat petani Indonesia in realizing food sovereignty, starting from advocating on the issues faced by serikat petani Indonesia and conducting community campaigns, education and training for serikat petani Indonesia, and koperasi as a platform to implement economic activities for serikat petani Indonesia.